1999
DOI: 10.1063/1.370717
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of the properties of heteroepitaxial Y2O3 films grown on Si by ion assisted evaporation

Abstract: Heteroepitaxial growth behavior of SrRuO 3 / SrTiO 3 (001) by pulsed laser depositionHeteroepitaxial Y 2 O 3 films were grown on an Si͑111͒ substrate by ion assisted evaporation in an ultrahigh vacuum, and their properties such as crystallinity, film stress, and morphological change were investigated using the various measurement methods. The crystallinity was assessed by x-ray diffraction ͑XRD͒ and reflection high-energy electron diffraction. Interface crystallinity was also examined by Rutherford backscatter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…This fact suggests that the probability of the occupancy of Eu 3 þ at the C 2 sites increases upon thermal treatment in oxygen atmosphere, therefore favoring the formation of electric dipoles. In this manner, we confirmed that the electric dipole transitions are hypersensitive to the ligand environment, as already indicated in the literature [18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This fact suggests that the probability of the occupancy of Eu 3 þ at the C 2 sites increases upon thermal treatment in oxygen atmosphere, therefore favoring the formation of electric dipoles. In this manner, we confirmed that the electric dipole transitions are hypersensitive to the ligand environment, as already indicated in the literature [18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Resultssupporting
confidence: 89%
“…The growth of these Eu:Y 2 O 3 films can yield Y 2 O 3 (1 1 0) [17,18] or Y 2 O 3 (1 1 1) on Si (1 0 0) [19], and similar behavior was also observed by Jones et al [20]. Similarly, films grown on Si (1 1 1) show a preferred (1 1 1) direction [21,22]. Therefore, from our experimental conditions, a pronounced difference between the peaks in the (4 0 0) and (4 1 1) directions for the Y 2 O 3 compound was observed prior to the thermal treatment, and this behavior was closely related to the type of substrate used ( Fig.…”
Section: Resultssupporting
confidence: 77%
“…A variety of physical and chemical methods have been used over the past decade to synthesize dielectric Y 2 O 3 films. These include methods such as chemical vapor deposition (CVD), rf magnetron sputtering, ion-assisted evaporation, anodization, electron-beam evaporation, sol−gel techniques, and reactive synthesis and undoped 2 Y 2 O 3 films.…”
Section: Introductionmentioning
confidence: 99%
“…The change of the lattice constant of the LAO films is mainly because the film was forced by compressive stress during the annealing process, which resulted from the variation of the film density. During the annealing process, the thermal energy provided to the atoms of LAO films migrated further into the site with the minimized energy, then high crystallinity of LAO film was obtained and film density was increased [21].…”
Section: Resultsmentioning
confidence: 99%